2018
DOI: 10.5937/jaes16-16494
|View full text |Cite
|
Sign up to set email alerts
|

Studies on concrete by partial replacement of cement with volcanic ash

Abstract: This paper presents the study on the volcanic ash as replacement of cement on compression strength of concrete. Preliminary study at the early stage were conducted with the specifi c gravity and sieve analysis of the volcanic as replacement of cement material of concrete. The cement replacement is made with the weight of the volcanic ash in the cement ratio of 2%, 4%, 6%, and 8%. Compressive strength test of concrete was conducted at the age of 7, 14, and 28 days. The mechanical properties by applying slump va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
4
0
3
Order By: Relevance
“…The chemical properties of this material make this a strong cementitious material with a comparable compressive strength to traditional concrete mixture designs with ranges of 6% to 10% replacement of Portland cement [28]. Interestingly, cure time for this material is roughly comparable to traditional concrete [29]. It is also important to note that one study identified volcanic ash as beneficial in improving the ability of concrete to resist freeze-thaw cycles with limited mass loss ratios (2.1-2.3%) [30], which is extremely important in regions with fluctuating temperatures, like New England.…”
Section: Synopsis Of Existing Literaturementioning
confidence: 92%
“…The chemical properties of this material make this a strong cementitious material with a comparable compressive strength to traditional concrete mixture designs with ranges of 6% to 10% replacement of Portland cement [28]. Interestingly, cure time for this material is roughly comparable to traditional concrete [29]. It is also important to note that one study identified volcanic ash as beneficial in improving the ability of concrete to resist freeze-thaw cycles with limited mass loss ratios (2.1-2.3%) [30], which is extremely important in regions with fluctuating temperatures, like New England.…”
Section: Synopsis Of Existing Literaturementioning
confidence: 92%
“…Abu vulkanik dari erupsi Gunung Sinabung dapat digunakan sebanyak 5% sebagai pengganti semen untuk mendapatkan beton struktural [9]. Bahkan hasil penelitian [10], peningkatan kuat tekan beton dengan abu vulkanik Gunung Sinabung hanya terjadi pada campuran 2%. Butiran halus abu vulkanik dapat mengisi rongga di antara agregat, sehingga mengurangi rongga dan meningkatkan kuat tekan beton [11].…”
Section: Pendahuluanunclassified
“…Penggunaan abu vulkanik erupsi Gunung Sinabung sebagai pengganti sebagian semen dengan campuran di atas 5% terhadap berat semen dapat menghasilkan beton struktural (Sudarmadji dan Hamdi 2014). Sedangkan abu vulkanik Gunung Sinabung dapat meningkatkan kekuatan tekan beton pada campuran 2-4% (Susanti, Tambunan, et al 2018) Abu vulkanik Merapi dapat dimanfaatkan sebagai bahan campuran dalam pembuatan bahan-bahan konstruksi seperti beton (Kurniawan, Sebayang, dan Muljadi 2011). Nilai kekuatan tekan beton tertinggi yang didapatkan akibat penggantian sebagian semen dengan abu vulkanik 10% adalah 29,65 MPa lebih tinggi 5,46% daripada kekuatan tekan beton normal yang hanya 28,115 MPa (Ariyani dan Luser 2013).…”
Section: Pendahuluanunclassified
“…Benda uji ini direndam dan dibiarkan selama 7 hari, 14 hari, 21 hari, dan 28 hari sebelum diuji dengan kekuatan tekan beton. Setiap variasi benda uji terdiri dari 3 sampel uji sesuai penelitian (Susanti, Tambunan, et al 2018). Sehingga jumlah benda uji yang diperlukan masing-masing umur beton sebanyak 3 x 4 benda uji x 5 variasi campuran dengan total benda uji 60 benda uji termasuk beton normal tanpa pencampuran abu vulkanik dan bottom ash.…”
Section: Pendahuluanunclassified